2019
DOI: 10.3390/molecules24030515
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Three New Phytotoxins from the Fungus Aspergillus nidulans by Pathway Inactivation

Abstract: Fungi are a source of novel phytotoxic compounds to be explored in the search for effective and environmentally safe herbicides. The genetic inactivation of the biosynthetic pathway of the new phytotoxin cichorine has led to the isolation of three novel phytotoxins from the fungus Aspergillus nidulans: 8-methoxycichorine (4), 8-epi-methoxycichorine (5), and N-(4’-carboxybutyl) cichorine (6). The structure of the new compounds was clearly determined by a combination of nuclear magnetic resonance (NMR) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly 6-hydroxy-4methoxy-5-methylphthalimidine (2) was isolated from Aspergillus silvaticus (Ageta and Ageta 1984;kawahara et al 1988), and later it was re-isolated from Alternaria cichorii, and was named cichorine (2) (Stierle et al 1993), but again no activity has been reported for this compound. Compounds 1 and 2 isolated as new natural products, but were never tested for their medicinal potential, however, newer analogues 8-methoxycichorine (3), 8-epi-methoxycichorine (4), and N-(4'-carboxybutyl) cichorine (5) (Liao et al 2019), separated through genetic inactivation of cichorine biosynthetic pathway in Aspergillus nidulans strain LO8030, were identified as phytotoxic and could be candidates for herbicide development. A genetic dereplication strategy in the fungus A. nidulans also produced a hybrid metabolite aspercryptin (6) (Chiang et al 2016), which is a cichorine-derived hexapeptide with 2-aminododecanol and 2-aminocaprylic acid residues.…”
Section: Phthalimidines From Ascomycetementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly 6-hydroxy-4methoxy-5-methylphthalimidine (2) was isolated from Aspergillus silvaticus (Ageta and Ageta 1984;kawahara et al 1988), and later it was re-isolated from Alternaria cichorii, and was named cichorine (2) (Stierle et al 1993), but again no activity has been reported for this compound. Compounds 1 and 2 isolated as new natural products, but were never tested for their medicinal potential, however, newer analogues 8-methoxycichorine (3), 8-epi-methoxycichorine (4), and N-(4'-carboxybutyl) cichorine (5) (Liao et al 2019), separated through genetic inactivation of cichorine biosynthetic pathway in Aspergillus nidulans strain LO8030, were identified as phytotoxic and could be candidates for herbicide development. A genetic dereplication strategy in the fungus A. nidulans also produced a hybrid metabolite aspercryptin (6) (Chiang et al 2016), which is a cichorine-derived hexapeptide with 2-aminododecanol and 2-aminocaprylic acid residues.…”
Section: Phthalimidines From Ascomycetementioning
confidence: 99%
“…The DcicB and the DcicC knockout strains produced the biosynthetic intermediates 3-methylorsellinic acid (217) and nidulol (218), respectively. The cichorine analogs 3-5 are also products of the cicF, which provides the basic phthalimidine backbone (Liao et al 2019). However, 3 and 4 feature an additional methoxy group at C-8, probably introduced at a later stage mediated by tailoring enzymes, e.g.…”
Section: Biosynthetic Studies In Aspergillus Nidulansmentioning
confidence: 99%
“…Additionally, 8-methoxycichorine, 8-epi-methoxycichorine, and N-(4′-carboxybutyl) cichorine, three novel cichorine analogues with an isoindolinone skeleton, obtained from A . nidulans , exhibited superior phytotoxicity to cichorine on the leaves of Zea mays and Medicago polymorpha [ 14 ]. Dihydrosterigmatocystin, isolated from an alga-derived fungus, Aspergillus versicolor , caused leaf necrosis and plant wilting in Amaranthus retroflexus , with a MIC of 24.5 μM, i.e., almost four-fold stronger than that of glyphosate [ 15 ].…”
Section: Introductionmentioning
confidence: 99%